Video-rate remote refocusing through continuous oscillation of a membrane deformable mirror. (20th October 2021) - Wright, Terry; Sparks, Hugh; Paterson, Carl; Dunsby, Chris
Abstract: This paper presents the use of a deformable mirror (DM) configured to rapidly refocus a microscope employing a high numerical aperture (NA) objective lens. An Alpao DM97-15 membrane DM was used to refocus a 40×/0.80 NA water-immersion objective through a defocus range of −50–50 μ m at 26.3 sweeps s −1 . We achieved imaging with a mean Strehl metric of >0.6 over a field of view in the sample of 200 × 200 μ m 2 over a defocus range of 77 μ m. We describe an optimisation procedure where the mirror is swept continuously in order to avoid known problems of hysteresis associated with the membrane DM employed. This work demonstrates that a DM-based refocusing system could in the future be used in light-sheet fluorescence microscopes to achieve video-rate volumetric imaging.